Laichgebiete des Dorschs in der westlichen Ostsee - Bleil, Martina; Oeberst, Rainer (2000)
Analyses of the previous years showed that the reproductionof the Belt Sea cod stock (Gadus morhua morhua) is also very important for the cod stock of the central BalticSea (Gadus morhua calarias). Oeberst (1999, 2000) proved, that between 20 % and 50 % of the cods caught in the Bornholm Sea at the age of 2 or 3 years between 1994 and 1998, were spawned in the Belt Sea. On account of this large significance of the Belt Sea cod stock, information regarding the reproduction process are important. The goal of the article presented is the description of the actual spawning areas of the Belt Sea cod stock by means of the spatial distribution of the spawners based on characteristic parameters as the maturity stages andthe proportion of the sexes. The basis for these analysesare data sampled between 1992 and 1999. The analyses showed that the actual main spawning areas in the western Baltic Sea were the deeper regions of the Kiel Bay, of the Fehmarn Bay and of the western Mecklenburg Bay. In these regions spawning cods were regularly observed with high intensity. Furthermore, the deeper basin of the Arkona Sea is an important spawning area.